Peranan Karakteristik Dewan Direksi dan Struktur Kepemilikan dalam Pengungkapan Sukarela Perusahaan Publik Indonesia - Yeo, Jessica; Suparman, Meiliana (Jurnal Ilmiah Akuntansi Kesatuan, 2021)
The objective of this study is to demonstrate that characteristics of the board of directors and ownership structure influence the level of voluntary disclosure. Board of directors’ characteristics include the board's size, composition, frequency of meetings, gender, expertise, and compensation. These attributes reflect the ownership structure, which includes foreign ownership, institutional ownership, and director ownership. Control variables include company size, firm age, leverage, profitability, and liquidity. This study utilized secondary data from 52 consumer goods companies listed on the Indonesia Stock Exchange for the period 2016 to 2020. In total, 228 observations were tested for hypotheses, after 32 outliers were removed from the data. The hypotheses were tested using panel regression with a Fixed Effect Model (FEM). The study found that all independent variables simultaneously have a significant impact on voluntary disclosures. According to the partial test (t-test), only the remuneration of directors and institutional ownership had a significant and positive effect on voluntary disclosures, while other variables had no significant impact. In addition, the foreign ownership variable had a significant affect on voluntary disclosure, however the direction is negative.